2014
DOI: 10.4236/health.2014.614214
|View full text |Cite
|
Sign up to set email alerts
|

Health Professionals’ Attitudes towards Electronic Psychosocial Assessments in Youth Mental Healthcare

Abstract: Psychosocial assessments can help mental health professionals establish good therapeutic relationships while simultaneously conducting holistic assessments of their young clients. Using technology to conduct assessments may increase disclosure by young people; however, the uptake of new technologies into current face-to-face practice has been slow. In the current study, we were interested in exploring the attitudes of mental health workers to using an electronic psychosocial assessment tool (e-tool) within fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 42 publications
0
8
2
Order By: Relevance
“…myAssessment was developed using human-centered design principles [ 34 ] which involved extensive research with stakeholders in order to determine functionality requirements and attitudes and beliefs around such an application [ 25 , 35 , 36 ]. In addition to the previously identified benefit of potentially obtaining higher rates of initial disclosure [ 29 ], this preparatory research highlighted other possible benefits and concerns.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…myAssessment was developed using human-centered design principles [ 34 ] which involved extensive research with stakeholders in order to determine functionality requirements and attitudes and beliefs around such an application [ 25 , 35 , 36 ]. In addition to the previously identified benefit of potentially obtaining higher rates of initial disclosure [ 29 ], this preparatory research highlighted other possible benefits and concerns.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the previously identified benefit of potentially obtaining higher rates of initial disclosure [ 29 ], this preparatory research highlighted other possible benefits and concerns. Both young people and clinicians felt that by using the application prior to the first appointment, young people would be given increased control in the treatment process as they could organize their thoughts and indicate what it was that they most wanted to speak about via a ‘flagging’ function [ 25 , 35 , 36 ]. Both groups also felt that the application would offer greater time efficiency as they could focus more on the important issues in session and spend less time on gathering less necessary information [ 25 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…in a systematic review showed that adolescents considered a self‐administered tool to be much more acceptable than face‐to‐face interview, which relies on direct disclosure of personal and intimate details to a relative stranger. Furthermore, digital survey tools were identified as possible solutions that could help engage young people who were not comfortable with interpersonal communication or talking about psychosocial stresses, and increased their perception of confidentiality . A survey of young people supported the use of an electronically administered questionnaire, as respondents could disclose concerns without fear of judgement by health professionals, and also provided young people with more control over the assessment …”
mentioning
confidence: 99%
“…In their feasibility study with 80 adolescents, 99% completed the survey, 92% found it easy to understand and easy to use, 91% felt comfortable or very comfortable with the content of the questions asked, 9% felt neutral and none felt uncomfortable . TickiT implements the desirable aspects of perceived privacy and control without judgement, identified in previous studies . A limitation of the TickiT platform is that while its usability has been demonstrated, its effectiveness for the HEEADSSS assessment is yet to be evaluated.…”
mentioning
confidence: 99%